THE VARIOUSITY OF HAPPINESS PERSPECTIVE AND ITS IMPLEMENTATION IN LEARNING PROCESS - Zuhdiyah Zuhdiyah; Asri Karolina; Fitri Oviyanti; Noza Aflisia; Yesa Satriya Dwi Hardiyanti (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
Happiness is the ultimate goal of all activities. The desire for happiness makes humans look for the source of happiness that its existence is worthy of several elements of life. Education as one of the crucial elements of life has varied learning models that can increase the willingness of students to learn. The conscious effort to learn becomes more optimal in a happy psychological condition. This research discusses the ultimate happiness in the Koran described with scientific theories of happiness and explains the Quantum theory of happiness in the learning model. The research method used was literature study and content analysis as the data analysis technique. The results of this study indicate that first, happiness in the Koran was not caused by wealth but our faith as a believer. Second, there are endorphins in humans that emit happiness and calmness. Third, someone who is happy will have a change in thoughts, words, actions, facial expressions, and positive muscle activity. Fourth, the learning model that can create happy learning begins with creating happy emotions, giving both material and non-material rewards, and good habituation. Fifth, the understanding about happiness from various perspectives can provide a variety of positive developments in all aspects of life and will lead into a better life.